2019
DOI: 10.1016/j.eclinm.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Perfusion Predicts Response to Sertraline versus Placebo for Major Depressive Disorder in the EMBARC Trial

Abstract: Background Major Depressive Disorder (MDD) has been associated with brain-related changes. However, biomarkers have yet to be defined that could “accurately” identify antidepressant-responsive patterns and reduce the trial-and-error process in treatment selection. Cerebral blood perfusion, as measured by Arterial Spin Labelling (ASL), has been used to understand resting-state brain function, detect abnormalities in MDD, and could serve as a marker for treatment selection. As part of a larger trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
2
29
1
1
Order By: Relevance
“…Cerebral perfusion can also be measured using arterial spin labeling in an MRI and was recently shown to predict SSRI response (131). In a sample of 231 patients with Major Depressive Disorder, increased perfusion in the putamen, anterior insula, inferior temporal gyrus, parahippocampal gyrus, inferior parietal lobule, and the orbitofrontal cortex predicted a positive response to the SSRI antidepressant sertraline (131). Further studies of the value of cerebral perfusion neuroimaging, using SPECT and arterial spin labeling in guiding effective treatment are ongoing.…”
Section: Well-established Diagnostic Roles For Spect and Petmentioning
confidence: 99%
“…Cerebral perfusion can also be measured using arterial spin labeling in an MRI and was recently shown to predict SSRI response (131). In a sample of 231 patients with Major Depressive Disorder, increased perfusion in the putamen, anterior insula, inferior temporal gyrus, parahippocampal gyrus, inferior parietal lobule, and the orbitofrontal cortex predicted a positive response to the SSRI antidepressant sertraline (131). Further studies of the value of cerebral perfusion neuroimaging, using SPECT and arterial spin labeling in guiding effective treatment are ongoing.…”
Section: Well-established Diagnostic Roles For Spect and Petmentioning
confidence: 99%
“…Establishing Moderators and Biosignatures of Antidepressant Response for Clinical Care for Depression (EMBARC), another large multisite trial [33], provided interesting observations on sertraline and placebo response over 8 weeks of treatment, with about 300 neuroimaging datasets available for analysis. Responders to sertraline, as compared to placebo, were characterized by higher baseline connectivity within the default mode network (DMN), greater betweennetwork connectivity of the DMN and executive control networks [34], an abnormal pattern of baseline pretreatment ventro-striatal response to reward expectancy and prediction error [35], and abnormal perfusion across a number of structures [36]. Intriguingly, some brain patterns seemed to favour placebo over sertraline.…”
Section: Pregenual Anterior Cingulate Cortex (Pgacc): a General Respomentioning
confidence: 99%
“…Previous studies revealed a link between perfusion and depression, reporting both increases and decreases in perfusion in frontal, striatal, and limbic regions in the context of MDD ( Duhameau et al, 2010 , Li et al, 2018 , Lui et al, 2009 , Orosz et al, 2012 , Vasic et al, 2015 ). Another recent study found reduced cerebral blood flow (CBF) in the right parahippocampal gyrus, the thalamus, and fusiform and middle temporal gyri as well as the bilateral insula, and increased CBF in the bilateral inferior parietal lobules in depressed adults ( Cooper et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%